Effects of the Reduce Sedentary Time (ReSeT) program applying socio-ecological model on sedentary behaviors among office workers: 10.55131/jphd/2024/220119 - Outtarawichian, Wanwilai; Kalampakorn, Surintorn; Boonyamalik, Plernpit; Teerawattananon, Yot (Journal of Public Health and Development, 2024)
Sedentary behavior (SB) has been associated with non-communicable diseases and premature deaths. SB has wide-ranging adverse impacts on most office workers as the nature of their work requires prolonged sitting. Therefore, the purpose of this study was to examine the effects of the Reduce Sedentary Time (ReSeT) program using multilevel intervention approaches based on the Socio-Ecological model on the SB of office workers. A Quasi-experimental design with a comparison group was used. Office workers from two office-based departments in a university setting were purposively selected and divided into intervention (n=39) and control (n=39) groups. The intervention group received the ReSeT program for 3 months. Activities in reducing SB included motivating individuals to reduce SB using health information, smart watches, and video clips. The organizational measures including policies aimed at to reducing SB, as well as enhancements to the social and physical environment were reinforced. Participants in the control group received no intervention. SB time during work and non-work hours was assessed using ActiGraph for 7 days at baseline, post-intervention, and at 3 months follow-up. The data were analyzed by descriptive statistics, repeated measure ANOVA, paired t-test, R, and RStudio program. After implementing the ReSeT program, the intervention group showed a significant reduction in SB time both for work and non-work periods as compared to the baseline and the control group (p<0.05). The multilevel intervention approaches of SB addressing both individual and organizational factors were suitable for reducing SB time among office workers.